PENGARUH STRUKTUR AKTIVA, RISIKO BISNIS DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013 - Apriyanti, Herlina; Sitanggang, J. P. (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2015)
This study was conducted to proof the influence of asset structure, business risks, and firm size to capital structure in manufacturing industry registered at Indonesia stock exchanges in 2013. Population in this research 142 firms in manufacturing industry, and sample obtained amount 47 firms. Data was obtained from Finance Report 2013. The analysis technique used is multiple regression by SPSS 22.0 program and hypothesis testing t-statistic as well as F statistic. Result of this study shows that asset structure, business risks, and firm size simultaneously influence to capital structure with. Adjusted R2 amount of 0.125, which means that only 12,5% variance of capital structure can be described by 3 variables : asset structure, business risks, and firm size, while the rest 87.5% described by other variables out of this model. Partially, that asset structure and business risks have a positive and significant effect to capital stucture, while firm size has not significant effect to capital structure.